Functional Outcome of Intra-Articular Hyaluronic Acid Injection in Osteoarthritis of Knee Joint: Pharmaceutical Science-Orthopaedics - Shah, Dr Parthiv; R Sachapara, Dr Umang; S. Patil, Dr Nitin (International Journal of Life Science and Pharma Research, 2023)
Osteoarthritis/Osteoarthrosis (OA) defines an idiopathic, slowly progressive disease of the diarthrodial (synovial)joints. Intra-articular - Hyaluronic acid has been proposed to have many therapeutic mechanisms of action in the OA knee,including shock absorption, joint lubrication, anti-inflammatory effects, chondroprotection, proteoglycan synthesis, and cartilagematrix alterations. Thirty-six patients were selected for the proposed study based on eligibility criteria, study period, andfeasibility. Patients with clinical symptoms of osteoarthritis were screened based on inclusion (grades 1 and 2) and exclusioncriteria (previous history of trauma). Patients with grade I or II Osteoarthritis based on Kellegren & Lawrence grading weretaken up for the study. After obtaining informed consent, a structured interview schedule was administered to obtaininformation on their background characteristics and clinical and functional outcome of Osteoarthritis using VAS (Visual AnalogueScale) and WOMAC (The Western Ontario and McMaster Universities Osteoarthritis Index) tools. Following this, theintervention was done. All the patients were given a single injection(6ml) of high molecular weight Hyaluronic acid. This studywas done to verify safety and feasibility. Our findings suggest that intra-articular hyaluronic acid is safe for use with kneeosteoarthritis. While local and minor adverse events related to hyaluronic acid injection occurred, all symptoms disappearedwithin 48 hours.